Airflow Pathway Development as Affected by Soil Moisture Variability in Heterogeneous Soils. Issue 1 (28th January 2013) - Sakaki, Toshihiro; Schulte, Paul E.; Cihan, Abdullah; Christ, John A.; Illangasekare, Tissa H.
Abstract : Understanding how lateral airflow pathways develop in the unsaturated zone is important to address problems dealing with intrusion of contaminants in the form of vapor into buildings and subsurface structures. One of the key factors that contribute to the formation of these vapor pathways is the spatial and temporal variation of soil moisture saturation. The soil moisture in the unsaturated zone is expected to be affected by the mass and temperature boundary conditions at the land surface. We performed highly controlled laboratory experiments in an intermediate‐scale test tank to improve the basic understanding of the factors that contribute to development of such pathways. The tank was packed with different test sands in a layered configuration and the precipitation and thermal boundary conditions were controlled at the soil surface. A numerical model based on the COMSOL Multiphysics software was validated using the experimental data. This model was used to obtain insights into how the degree of subsurface heterogeneity affects air pathway development. The results showed that (i) soil moisture variations created by precipitation could significantly affect the development of dynamic airflow pathways, (ii) thermal flux at the soil surface does not significantly affect soil moisture deep in the formation and hence has a negligible effect on airflow pathways, and (iii) the capping effect created by water accumulating at soil layer interfaces results in more air of subsurface origin entering the building. Further study is needed, however, to examine the validity of these findings under more realistic soil and climate conditions.